SPECIFIC IMMUNITY TO ENDOTOXIN IN PATIENTS WITH EXACERBATIONS OF BRONCHIAL ASTHMA - Bisyuk, Yu.A. (World of Medicine and Biology, 2015)
The study included 331 patients with asthma. 4 or more exacerbations during the last year were considered a criterion for frequent asthma phenotype and 3 or less with infrequent exacerbations. Results of the study found that patients with frequent exacerbations characterized by the prevalence of female which were taking combination of inhaled corticosteroids and long-acting β2 agonists and the presence of severe bronchial obstruction in association with high levels of sCD14 in induced sputum.
Keywords: bronchial asthma; endotoxin; immunity